Optical measurements of long-range protein vibrations - Acbas, G.; Niessen, K. A.; Snell, E. H.; Markelz, A. G. (Nature Communications, 2014)
Protein biological function depends on structural flexibility and change. From cellular communication through membrane ion channels to oxygen uptake and delivery by haemoglobin, structural changes are critical. It has been suggested that vibrations that extend through the protein play a crucial role in controlling these structural changes. While nature may utilize such long-range vibrations for optimization of biological processes, bench-top characterization of these extended structural motions for engineered biochemistry has been elusive. Here we show the first optical observation of long-range protein vibrational modes. This is achieved by orientation-sensitive terahertz near-field microscopy measurements of chicken egg white lysozyme single crystals. Underdamped modes are found to exist for frequencies >10 cm(-1). The existence of these persisting motions indicates that damping and intermode coupling are weaker than previously assumed. The methodology developed permits protein engineering based on dynamical network optimization.
Keywords: absorption; crystals; dynamics; frequency raman-spectra; hydration; lysozyme; motions; Science & Technology - Other Topics; sensitivity; simulations; spectroscopy